Scoping review of ethnobotanical studies on Piliostigma thonningii (Schumach.) Milne-Redh. in Sub-Saharan Africa - Nethathe, Bono; Ramphinwa, Lonia Maanea; Selekane Motadi, Ananias; Matlakala, Frans Koketso (Frontiers in Pharmacology, 2025)
Background:Piliostigma thonningii is a plant commonly used in traditional medicinal practices throughout Sub-Saharan Africa for the treatment of various ailments, such as respiratory infections, gastrointestinal and inflammatory disorders. Several studies have documented ethnobotanical uses of this plant in different countries in Sub-Saharan Africa.Aim:This study critically reviews the ethnobotanical uses mainly focusing on traditional medicinal uses of P. thonningii in Sub-Saharan Africa.Methods:A scoping review following the guidelines of Arksey and O’Malley was used to conduct this study. Various databases were used for searching for relevant articles and were handled in the reference manager EndNote. The data extraction focused on the links between P. thonningii and ethnobotanical uses in Sub-Saharan Africa. A descriptive analysis highlighted the years of publication, countries of publication, study designs, study participants, plant parts used, the diseases treated or managed, and how the plants are prepared or administered.Results:Of the 46 countries in Sub-Saharan Africa, only 14 have published studies on the ethnobotanical uses of P. thonningii. Notably, Nigeria emerged as a leader in this field, with the most publications. The results also highlight that leaves are the most common part of the plant used and that remedies are mostly prepared as a decoction, with the plant being popularly used to treat malaria.Conclusion and recommendation:This scoping review provides a comprehensive overview of traditional healing practices using P. thonningii in Sub-Saharan Africa and reveals substantial knowledge gaps across the region. However, the study revealed limitations such as lack of standardization on methods used to prepare remedies and dosages.